1998
DOI: 10.1002/ana.410440412
|View full text |Cite
|
Sign up to set email alerts
|

Acquired slow–channel syndrome: A form of myasthenia gravis with prolonged open time of the acetylcholine receptor channel

Abstract: A 32-year-old female presented with a 2-year history of fluctuating generalized weakness including extraocular, bulbar, and limb muscles, suggesting myasthenia gravis, but with poor response to pyridostigmine and unusual electromyographic findings. After rest, power increased on repeated maximal contractions, followed by progressive weakness. There were decremental responses at low-frequency stimulation, but incremental responses at high frequencies, and single stimuli evoked repetitive compound muscle action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…Autoantibodies against the γ subunit of the AChR which is only present in embryonic forms of the receptor have been reported in some cases to block the AChR function and cause arthrogryposis multiplex congenita (67). Conversely, AChR antibodies can also induce prolonged open time of the AChR leading to muscle weakness by excitotoxicity at the neuromuscular junction (68). Anti-AMPAR (GluR3B subunit) autoantibodies (anti-AMPA-GluR3B) can activate AMPAR that contains the GluR3B subunit, leading to the spontaneous occurrence of ion currents (69, 70).…”
Section: Igg Effector Functionsmentioning
confidence: 99%
“…Autoantibodies against the γ subunit of the AChR which is only present in embryonic forms of the receptor have been reported in some cases to block the AChR function and cause arthrogryposis multiplex congenita (67). Conversely, AChR antibodies can also induce prolonged open time of the AChR leading to muscle weakness by excitotoxicity at the neuromuscular junction (68). Anti-AMPAR (GluR3B subunit) autoantibodies (anti-AMPA-GluR3B) can activate AMPAR that contains the GluR3B subunit, leading to the spontaneous occurrence of ion currents (69, 70).…”
Section: Igg Effector Functionsmentioning
confidence: 99%
“…Repetitive muscle discharge in response to a single nerve stimulus usually implies re‐excitation of muscle fibers by prolonged EPPs 3, 6, 7, 9. This is seen not only in congenital end‐plate AChE deficiency but also in other entities, such as organophosphate poisoning,1, 9 exposure to other anti‐acetylcholinesterases,3, 14 another form of congenital myasthenia called slow‐channel syndrome,6 and acquired slow‐channel syndrome 16. All of these conditions are characterized by prolonged end‐plate depolarization, which results from excess ACh caused by depression of AChE or abnormal channel kinetics of receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is conceivable that the ability of the muscle to compensate for the loss of nAChR and its associated proteins during the attack by anti-nAChR antibodies ultimately influences the severity of the disease [39]. Fourthly, some antibodies may interfere with the function of the muscle nAChR, and it has been reported that antibodies can block the binding of ACh [40,41] or affects the opening of the ion channel [42,43].…”
Section: Antibodies Against the Nachrmentioning
confidence: 96%
“…Apparently, the antibody was directed to the 1-subunit of the adult nAChR or its interface with neighboring subunits [43].…”
Section: Antibodies In Idiopathic Mgmentioning
confidence: 99%